2016
DOI: 10.1089/ham.2015.0084
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiometabolic Risk and Worsening Hypoxemia at High Altitude

Abstract: . Increased cardiometabolic risk and worsening hypoxemia at high altitude. High Alt Med Biol. 17:93-100, 2016.-Metabolic syndrome, insulin resistance, diabetes, and dyslipidemia are associated with an increased risk of cardiovascular disease. While excessive erythrocytosis is associated with cardiovascular complications, it is unclear how worsening hypoxemia of any degree affects cardiometabolic risk factors in high-altitude populations. We studied the relationship between daytime resting oxyhemoglobin saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 49 publications
3
38
0
1
Order By: Relevance
“…Our findings suggest that the frequency of events rather than severity of nocturnal hypoxemia could account for glucose intolerance in these highlanders. In addition to recurrent SDB episodes, we confirmed our previous finding that sustained hypoxemia during wakefulness was also associated with HbA1c elevations [27] ( see Fig. 4, left column ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings suggest that the frequency of events rather than severity of nocturnal hypoxemia could account for glucose intolerance in these highlanders. In addition to recurrent SDB episodes, we confirmed our previous finding that sustained hypoxemia during wakefulness was also associated with HbA1c elevations [27] ( see Fig. 4, left column ).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, we have found unique associations between cardiometabolic outcomes, sleep-related breathing disturbances [26] and hypoxemia during wakefulness in Peruvian highlanders [27], suggesting a pathogenic role for SDB. We hypothesized that chronic and intermittent nocturnal hypoxemia are differentially associated with specific biomarkers of cardiometabolic dysfunction, viz., hemoglobin concentration and glucose levels, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The most recent reports on long-term high-altitude residents have shown increases in cardiometabolic risks (metabolic syndrome), where a higher BMI is associated with lower oxygen saturation [61]. In concordance with this, it has also been demonstrated that a strong association exists between being overweight or having metabolic syndrome and excessive erythrocytosis (CMS) [62].…”
Section: Obesity and Chronic Exposure To High Altitudementioning
confidence: 86%
“…Although it seems clear that obesity and overweight, according to current knowledge, exert their most deleterious effects by aggravating hypoxemia at high altitude, thereby triggering the development of high altitude illnesses [5,61], it is thus far not known how adipose tissue function and severe high-altitude hypoxemia interact. Further studies are required to further investigate this interaction.…”
Section: Hypoxia and Adipose Tissuementioning
confidence: 99%
“…In terms of the offspring, one of the outcomes of pre-eclampsia is a restriction of fetal growth, characterized by already well described long term consequences for increased risk of non-communicable diseases, including cardiovascular and metabolic conditions [7072]. Adding to the complexity offered by low- and middle-income settings, the observed pathophysiologic changes will be compounded with, and will require broader expansions to explicitly assess the human-environment interactions, particularly cardiovascular and metabolic adaptations to high-altitude settings [7377]. …”
Section: Challenges For Global Health Cardiologymentioning
confidence: 99%